2019
DOI: 10.1029/2019jd031028
|View full text |Cite
|
Sign up to set email alerts
|

Microphysics of Snowfall Over Coastal East Antarctica Simulated by Polar WRF and Observed by Radar

Abstract: The current assessment of the Antarctic surface mass balance mostly relies on reanalysis products or climate model simulations. However, little is known about the ability of models to reliably represent the microphysical processes governing the precipitation. This study makes use of recent ground‐based precipitation measurements at Dumont d'Urville station in Adélie Land to evaluate the representation of the precipitation microphysics in the Polar version of the Weather Research Forecast (Polar WRF) atmospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 89 publications
1
42
0
Order By: Relevance
“…As for the new ECMWF products, the polar WRF used in AMPS runs with a microphysics scheme based on five prognostic variables (WSM, Hong and others, 2004). Vignon and others (2019b) showed that polar WRF simulations, based on different state-of-the-art microphysical schemes, for two summertime precipitation events at DDU, show large discrepancies with respect to observations. Also, for results from MZS, some differences appear compared to the observations.…”
Section: Discussionmentioning
confidence: 99%
“…As for the new ECMWF products, the polar WRF used in AMPS runs with a microphysics scheme based on five prognostic variables (WSM, Hong and others, 2004). Vignon and others (2019b) showed that polar WRF simulations, based on different state-of-the-art microphysical schemes, for two summertime precipitation events at DDU, show large discrepancies with respect to observations. Also, for results from MZS, some differences appear compared to the observations.…”
Section: Discussionmentioning
confidence: 99%
“…This type of precipitation system is typical for DDU (Jullien et al, 2020). The accumulated precipitation at the ground during the event was 3.4 mm (Vignon et al, 2019a).…”
Section: Application Of the Methodology To Two Case Studiesmentioning
confidence: 81%
“…Albeit intriguing, the thin upper layer of SUB visible around 3000 m between 28 December at 14:00 UTC and 29 December at 09:00 UTC is likely explained by a sub-saturated layer with respect to ice visible in the radiosoundings (not shown, see Fig. 2h from Vignon et al (2019a)).…”
Section: Illustration Of the Methodsmentioning
confidence: 93%
“…As a first order approximation, we assume that the so called 'precipitating air parcels' in the ERA5 dataset are those for which the snow water content (SWC) vertical gradient in the column above DDU is significantly negative: dSW C/dz < SW C T where SW C T has been set to −1.5 10 −9 kg kg −1 m −1 after inspection of the distribution of dSW C/dz above DDU (not shown). The underlying reason is that if we neglect the advection -which is a reasonable hypothesis for Antarctic stratiform precipitation as the one over the Antarctic coast and given the ≈ 30 km horizontal resolution of ERA5 -a negative vertical gradient of SWC typically corresponds to a situation with auto-conversion of ice to snow or snowflake growth through vapor deposition, aggregation or riming (see Vignon et al, 2019a for examples above DDU). Examination of individual vertical profiles of SWC reveals that positive vertical gradients are almost always located in the katabatic layer, where sublimation occurs.…”
Section: Back-trajectories Of Precipitating Air Parcelsmentioning
confidence: 99%